Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas; Fritz, Marlon (Journal of Nonparametric Statistics)

Modern sector development: The role of exports and institutions in developing countries - Gries, Thomas; Grundmann, Rainer (Review of Development Economics)

Gender, competitiveness, and task difficulty: Evidence from the field - Hoyer, Britta; van Huizen, Thomas; Keijzer, Linda; Rezaei, Sarah; Rosenkranz, Stephanie; Westbrock, Bastian (Labour Economics)
This study examines the gender gap in competitiveness in an educational setting and tests whether this gap depends on the difficulty of the task at hand. For this purpose, we administered a series of experiments during the final exam of a university course. We confronted three cohorts of undergraduate students with a set of bonus questions and the choice between an absolute and a tournament grading scheme for these questions. To test the moderating impact of task difficulty, we (randomly) varied the difficulty of the questions between treatment groups. We find that, on average, women are significantly less likely to select the tournament scheme. However, the results show that the gender gap in tournament entry is sizable when the questions are relative easy, but much smaller and statistical insignificant when the questions are difficult.

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.